Pemodelan Jumlah Pengangguran Usia Muda di Provinsi Jawa Timur Tahun 2019 dengan Regresi Binomial Negatif - Agriyandi Rizaldi; Agung Priyo Utomo (Politeknik Statistika STIS, 2021)
Unemployment is an actual problem in employment in Indonesia. In 2019, the number of unemployment in Indonesia was 7,10 million people, 56,02 percent or 3,98 million of whom were the young age group (15-24 years old). Youth unemployment indicates a waste of limited human resources that can hinder potential economic growth. In addition, it also has an impact on the social environment, such as crime, health problems, and poverty. East Java was the province with the second highest number of youth unemployment in Indonesia as many as 478.478 people, even though the economy showed good growth, even better than the national economic growth during 2015-2019. This study aims to analyze the variables that affect the number of youth unemployment in East Java Province in 2019. The data used are Sakernas August 2019 (backcasting). The analytical method used is negative binomial regression because it can overcome overdispersion problem in Poisson regression. The results of analysis showed that there was significant effect of the variable regional minimum wage, labor absorption in agricultural and manufacturing sector, economic growth, and APK SMA on the number of youth unemployment. Meanwhile, variable percentage of young workforce who graduate high school/equivalent and invesment had no significant effect on the number of youth unemployment.